2004
DOI: 10.1074/jbc.m408149200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Is Required for the Lipid-lowering Effect of Metformin in Insulin-resistant Human HepG2 Cells

Abstract: The antidiabetic drug metformin stimulates AMP-activated protein kinase (AMPK) activity in the liver and in skeletal muscle. To better understand the role of AMPK in the regulation of hepatic lipids, we studied the effect of metformin on AMPK and its downstream effector, acetyl-CoA carboxylase (ACC), as well as on lipid content in cultured human hepatoma HepG2 cells. Metformin increased Thr-172 phosphorylation of the ␣ subunit of AMPK in a dose-and time-dependent manner. In parallel, phosphorylation of ACC at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
352
1
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(387 citation statements)
references
References 47 publications
22
352
1
12
Order By: Relevance
“…Hence, the cause of this effect remains unidentified. Incubation of HepG2 cells in a high glucose concentration was shown to induce insulin resistance [27], which may result in the observed disturbance of regulation of IDE activity by insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the cause of this effect remains unidentified. Incubation of HepG2 cells in a high glucose concentration was shown to induce insulin resistance [27], which may result in the observed disturbance of regulation of IDE activity by insulin.…”
Section: Discussionmentioning
confidence: 99%
“…FBS and either normal (1.0 g/l) or high (4.5 g/l) concentrations of D-glucose for 48-72 h to 80% confluence. Incubation of cells in high-glucose medium was used as a model of insulin resistance [27]. After 24 h of serum starvation cells were treated with 0.1, 1, 10, 100 or 200 nmol/l insulin (Sigma Aldrich, Taufkirchen, Germany) for 24 h. As an osmotic control, 3.64 g/l mannitol (Sigma Aldrich) was added to normal glucose medium in simultaneous wells.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment of HepG2 and HUVEC cells with metformin did not show any detectable cell toxicity. After 6 hours cells were washed twice with phosphate-buffered saline, and lysed in ice-cold buffer (20 mM Tris-HCl, pH 8.0, 1% Nonidet P-40, 1 mM EDTA, 1 mM EGTA, 1 mM sodium orthovanadate, 1 mM dithiothreitol, 1 mM phenylmethyl sulfonyl fluoride and 1 mM protease inhibitor cocktails (Sigma-Aldrich) [36]. Cells were scraped from the plates and collected in a micro-centrifuge tube.…”
Section: Rt-pcrmentioning
confidence: 99%
“…This was strengthened by showing that the metabolic effect of the drug is preserved in liver-specific AMPK-deficient mice (Viollet et al 2012). It is worth remembering that AMPK inhibits gluconeogenesis and glycogenolysis, stimulates glycogenesis in hepatocytes, and increases glucose uptake in peripheral tissues (Zang et al 2004, Zhou et al 2001. Besides the effects on the liver and skeletal muscle, studies have shown that metformin activates AMPK in aortic endothelial tissue in vivo (Zou et al 2004).…”
Section: Glucose Uptake Pathwaysmentioning
confidence: 99%